Spectrophotometric Determination of Dobutamine Hydrochloride in Pharmaceutical Formulations - Kanna Rao, K.V.; Reddy, M.N. (Asian Journal of Chemistry, 2010)
Two simple, sensitive and accurate visible spectrophotometric methods (A and B) have been developed for the determination of dobutamine hydrochloride either in pure form or in pharmaceutical formulations. Method A is based on the reduction of 1,2-naphthoquinone- 4-sulphonate, the well-known Follin's reagent, and method B is based on the oxidataion of DBH with excess ferric chloride and determining the consumed FeCI3 with K3Fe(CN)6. All of the variables have been optimized and the reactions presented.